Diffuse Large B-Cell Lymphoma of the Heart - Faizah Dwi Tirtasari; Budiarsinta; Rita Cempaka; Nungki Anggorowati; Nugira Dinantia (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) of the heart accounts for only 1% of primary cardiac tumors. Histopathology examination becomes the primary key for diagnosis and immunohistochemistry evaluation for defining non-Hodgkin lymphoma (NHL) subtype is able to predict the patient prognosis and treatment modality options. Case description: 70-year-old man complained of shortness of breath. Echocardiographic examination revealed mass occupied the left atrium measured 5.9 x 2.9 cm inherent with interatrial septum and mass with a stem in the right atrium measured 4.6 x 2.4 cm. Intraoperative, considerable amount of extracardiac mass was found, mass extension was unable to be determined. Thoracic surgeon decided to sample the extracardiac mass without performing cardiac surgery. The histopathologic features showed round blue cell tumor resembling a NHL. Immunohistochemical staining were consistent with diffuse NHL, large cell, high grade lymphoma, suitable for DLBCL. Discussion and conclusion: Round blue cell tumor of extracardiac mass with positive expression of LCA and CD 20 is suitable for B-cell non-Hodgkin lymphoma. Ki-67 immunohistochemical staining revealed a 70-80% proliferation index which indicates a high-grade lymphoma and defining diagnosis and treatment of DLBCL.